2015
DOI: 10.1007/s10900-015-0070-9
|View full text |Cite
|
Sign up to set email alerts
|

Oily Fish Intake and Cognitive Performance in Community-Dwelling Older Adults: The Atahualpa Project

Abstract: Due to their high content of omega-3 polyunsaturated fatty acids, oily fish consumption is likely associated with a better cognitive performance. However, information on this association is controversial, with some studies showing a positive effect while others showing no association. We aimed to assess the effects of oily fish consumption on cognitive performance in a population of frequent fish consumers living in rural coastal Ecuador. Atahualpa residents aged ≥60 years were identified during a door-to-door… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
13
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 29 publications
(14 citation statements)
references
References 37 publications
1
13
0
Order By: Relevance
“…Previous studies provided evidence that individuals with established AD do not get any benefit from this type of intervention [ 53 54 ] and yet individuals with MCI or AD in incipient stage could benefit from n-3 PUFA supplements [ 9 , 54 56 ]. On the other hand, the improvements detected are coherent with previous studies [ 3 , 9 , 57 62 ]. Therefore, the evidence still uncertain, especially, when the majority of the intervention studies were conducted on relative small samples.…”
Section: Discussionsupporting
confidence: 91%
“…Previous studies provided evidence that individuals with established AD do not get any benefit from this type of intervention [ 53 54 ] and yet individuals with MCI or AD in incipient stage could benefit from n-3 PUFA supplements [ 9 , 54 56 ]. On the other hand, the improvements detected are coherent with previous studies [ 3 , 9 , 57 62 ]. Therefore, the evidence still uncertain, especially, when the majority of the intervention studies were conducted on relative small samples.…”
Section: Discussionsupporting
confidence: 91%
“…This study detected a positive correlation between at least one serving of fish per week and slower declines in global cognitive function, composite and verbal memory scores. Finally, most recently del Brutto et al [ 200 ] reported on a cohort from a rural middle-to-low income area of Ecuador that cognitive function as measured by Montreal Cognitive Assessment (MoCA) scores was positively related to the number of fish servings per week, and the data suggested an intake of at least four fish servings per week was best.…”
Section: Dha and Cognition In Adulthood And Agingmentioning
confidence: 99%
“…The idea that low omega-3 PUFAs levels is linked to depression is supported by the observation that lower rates of depression are found in countries which have a higher fish consumption, a major source of dietary omega-3 PUFAs [100,101]. Furthermore, a wealth of studies has found an inverse relationship between consumption of fish and incidence of depression in various populations [102,103,104,105,106,107]. …”
Section: Polyunsaturated Fatty Acids (Pufas)mentioning
confidence: 99%